2004
DOI: 10.4049/jimmunol.173.10.6458
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the FcεRIβ Promoter Region Affecting Transcription Activity: A Possible Promoter-Dependent Mechanism for Association between FcεRIβ and Atopy

Abstract: The β subunit of the high-affinity IgE receptor (FcεRI) plays an important role in IgE-mediated allergic reactions as an amplifier for cell surface expression and signal transduction of FcεRI. FcεRIβ is presumed to be one of the genes linked with atopic diseases. However, the validity of the associations previously found between single nucleotide polymorphisms (SNPs) in FcεRIβ and atopic diseases is questionable. In the present study, we found correlation between the SNP of FcεRIβ at +6960A/G, resulting in a G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 32 publications
(40 reference statements)
3
46
0
Order By: Relevance
“…A more recent study showed that FcR ␤T isoform competed with the wild-type FcR ␤-subunit during Fc⑀RI assembly in the endoplasmic reticulum preventing proper folding of Fc⑀RI ␣-chain, and it seemed that cotranslational endoplasmic reticulum assembly of Fc⑀RI controlled the formation of a functional IgE-binding Fc⑀RI (27). A subsequent report has also described two single nucleotide polymorphism mutations in potential transcription binding sites of FcR ␤ promoter region that enhanced its gene expression (80). Collectively, these data provide a potential connection between FcR ␤ polymorphisms, Fc⑀RI expression, and atopy.…”
Section: Fc⑀ri Regulationmentioning
confidence: 94%
“…A more recent study showed that FcR ␤T isoform competed with the wild-type FcR ␤-subunit during Fc⑀RI assembly in the endoplasmic reticulum preventing proper folding of Fc⑀RI ␣-chain, and it seemed that cotranslational endoplasmic reticulum assembly of Fc⑀RI controlled the formation of a functional IgE-binding Fc⑀RI (27). A subsequent report has also described two single nucleotide polymorphism mutations in potential transcription binding sites of FcR ␤ promoter region that enhanced its gene expression (80). Collectively, these data provide a potential connection between FcR ␤ polymorphisms, Fc⑀RI expression, and atopy.…”
Section: Fc⑀ri Regulationmentioning
confidence: 94%
“…We previously demonstrated that the transcription of genes encoding FcεRIa and FcεRIb is positively regulated by the transcription factors PU.1, GATA-1, and GATA-2 in mast cells (3,5,7,(38)(39)(40)(41). Additionally, GATA-2 also plays an important role in the transcription of the Kit gene (11).…”
Section: Tgf-b1 Suppresses Fc«ri and C-kit Expression In Mast Cellsmentioning
confidence: 99%
“…For sorting of c-kitpositive or c-kit/Fc⑀RI-double-positive cells, BD FACSAria Cell Sorter (BD Biosciences, San Jose, CA) was used. Cells stained with each Ab, as described previously (23,24), were analyzed by FACSCalibur flow cytometer (BD Biosciences).…”
Section: Flow Cytometric Analysismentioning
confidence: 99%